Kansas Populism Ideas and Men - Clanton, O. Gene (University Press of Kansas, 1969)
Because Kansas has been called "the leading Midwestern Populist state," and the Midwestern phrase was the principle one of this significant movement in American history, this first comprehensive history of the Kansas People's party, its leaders, and their thoughts and actions is an important addition to Populist historiography. Through this study of the leadership, as well as a complete and personal background analysis of the Populist and Republican members of five Kansas legislatures, the author helps to place Populism within its proper historical context.Although Kansas Populism is shown to have had a retrogressive strain, the pervasive force of the movement is revealed as a constructive and progressive response to the technological achievements that had revolutionized agriculture and industry over the course of the nineteenth century. Their answers were not always commendable, but the Populists were the first political activists to come to grips in an effective manner with the problems created by the continuing economic revolution that uniquely characterizes modern history, and they were "intent on demonstrating, apparently, that the purification of politics was not an iridescent dream." In the dialogue which they conducted, in the program which they advance, they assisted in launching a progressive quest that continues in our own time.Undertaken with the objective of testing recent controversial interpretations of the Populist movement, this book, according to one reader, "far surpasses" studies of Populism in other states "done long ago and innocent of modern methods." It contains passages "almost epigrammatic in their perceptiveness" and is notable for the author's "fairness in dealing with the evidence." In fact, the breadth of research and the extensive annotation and bibliographical material included make this volume an important source in itself.